The Association Between the Physical State of Homes and PHBS and the Prevalence of Pulmonary Tuberculosis in the Lubuk Buaya Health Center's Working Area in Padang City - Kalasta Ayunda Putri; Tania Varera; Aulia Rahma Cheni (Miracle Journal Get Press, 2024)
Tuberculosis (TB) remains a major global public health problem, with 58% of cases occurring in men, 32% in women, and 10% in children (Global Tuberculosis Report, 2021). In Padang City, 1,199 TB cases were reported in 2021, with the highest number in Lubuk Buaya. This study aimed to analyze the relationship between pulmonary TB incidence, housing conditions, and clean and healthy living behavior (PHBS).This quantitative study used a descriptive-analytic case-control design involving 27 cases and 27 controls. The results showed that adequate environmental conditions included humidity (46.3%), ventilation (51.9%), and lighting (61.1%), while good PHBS was found in 33.3% of respondents. Bivariate analysis using the Chi-square test indicated significant relationships between TB incidence and humidity (p=0.029; OR=4.038), ventilation (p=0.014; OR=4.750), lighting (p=0.026; OR=4.375), and PHBS (p=0.009; OR=6.129).In conclusion, housing conditions and PHBS are significantly associated with TB incidence. Therefore, improving healthy housing conditions and strengthening health education on sanitation and PHBS are essential to prevent TB transmission in the community.